Nanotechnology—Applications in Prosthodontics: A Literature Review - Thomas, Benny; Mathew, CA; Muthuvignesh, J (Journal of Orofacial Research, 2014)
Nanoscale particles are not new to nature or science. However, the recent leaps in areas, such as microscopy have given scientists new tools to understand and take advantage ofphenomena that occur naturally when matter is organized at the nanoscale. Nanotechnology is not simply working at ever smaller dimensions; rather, working at the nanoscale enablesscientists to utilize the unique physical, chemical, mechanical, and optical properties of materials that naturally occur at that scale. In this article, we have made an attempt to have an early glimpse on impact of nanotechnology in the field of dentistry.